Time-lapse lens-free imaging of cell migration in diverse physical microenvironments. Issue 17 (20th July 2016) - Mathieu, Evelien; Paul, Colin D.; Stahl, Richard; Vanmeerbeeck, Geert; Reumers, Veerle; Liu, Chengxun; Konstantopoulos, Konstantinos; Lagae, Liesbet
Abstract : Lens-free imaging using coherent illumination is established as an inexpensive and reliable alternative to conventional phase contrast microscopy for live-cell imaging applications. Abstract : Time-lapse imaging of biological samples is important for understanding complex (patho)physiological processes. A growing number of point-of-care biomedical assays rely on real-time imaging of flowing or migrating cells. However, the cost and complexity of integrating experimental models simulating physiologically relevant microenvironments with bulky imaging systems that offer sufficient spatiotemporal resolution limit the use of time-lapse assays in research and clinical settings. This paper introduces a compact and affordable lens-free imaging (LFI) device based on the principle of coherent in-line, digital holography for time-lapse cell migration assays. The LFI device combines single-cell resolution (1.2 μm) with a large field of view (6.4 × 4.6 mm 2 ), thus rendering it ideal for high-throughput applications and removing the need for expensive and bulky programmable motorized stages. The set-up is so compact that it can be housed in a standard cell culture incubator, thereby avoiding custom-built stage top incubators. LFI is thoroughly benchmarked against conventional live-cell phase contrast microscopy for random cell motility on two-dimensional (2D) surfaces and confined migration on 1D-microprinted lines and in microchannels using breast adenocarcinoma cells. The quality of the results obtained by the two imaging systems is comparable, and they reveal that cells migrate more efficiently upon increasing confinement. Interestingly, assays of confined migration more readily distinguish the migratory potential of metastatic MDA-MB-231 cells from non-metastatic MCF7 cells relative to traditional 2D migration assays. Altogether, this single-cell migration study establishes LFI as an elegant and useful tool for live-cell imaging.